ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGANTIAN KANTOR AKUNTAN PUBLIK SECARA VOLUNTARY (Studi Empiris pada Perusahaan Keuangan yang terdaftar di BEI) - Firyana, Rachma Aulia; Septiani, Aditya (Diponegoro Journal of Accounting, 2014)
Auditor independence issue often triggers debate regarding auditor rotation. ThisÂ auditorÂ rotationÂ isÂ relatedÂ withÂ companyÂ actionÂ toÂ doÂ auditor switching. ThisÂ researchÂ aimsÂ toÂ knowÂ empiricalÂ evidenceÂ asÂ forÂ factorsÂ influencing auditor Â switchingÂ onÂ the financial firmÂ listedÂ inÂ IndonesiaÂ StockÂ Exchange. The factors to be analysed in this research are managementÂ change,Â financialÂ distress, client size,Â firm size, and percentage of ROA changes. The data beingÂ usedÂ isÂ from financial companyÂ whichÂ isÂ listedÂ in â€œBursa Efek Indonesiaâ€ (BEI) in 2007-2012 period. Data collecting method which used in this research is method purposive sampling, that based on criteria which has been determined before. Based on the method purposive sampling, research sample total is 115 companies. By using logistic regression,Â thisÂ researchÂ triedÂ toÂ testÂ effectÂ ofÂ managementÂ changes, financialÂ distress, client size, firm size, and percentage of ROA changes towards Auditor Switching.Â Result of this research indicates that variable having which significantly effect the voluntary auditor switching are managementÂ change,Â firm size, and percentage of ROA changes. On the other hand, other variables like financialÂ distress andÂ client size do not have significant effect on company decision to do voluntary auditor switching.Â